2004
DOI: 10.1080/00207590344000196
|View full text |Cite
|
Sign up to set email alerts
|

Human rights and ethnic attitudes in Spain: The role of cognitive, social status, and individual difference factors

Abstract: Cognitive, individual differences, and intergroup contact factors were examined in the formation of attitudes about human rights and ethnic bias in two studies conducted in Spain. A 7‐item scale measuring knowledge about human rights laws in Spain and the European Union was used in both studies. Participants were university students enrolled at the Universidad Autónoma de Madrid. In study one, participant (n = 127) knowledge about human rights laws, intergroup contact, Right Wing Authoritarianism (RWA), and Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Positive feelings about hate crime laws would be predicted by possession of accurate knowledge of human rights laws, when controlling for participant age, gender, and political orientation. This would cross‐culturally replicate the Dunbar et al (2004) findings.…”
Section: Research Questionsmentioning
confidence: 78%
See 4 more Smart Citations
“…Positive feelings about hate crime laws would be predicted by possession of accurate knowledge of human rights laws, when controlling for participant age, gender, and political orientation. This would cross‐culturally replicate the Dunbar et al (2004) findings.…”
Section: Research Questionsmentioning
confidence: 78%
“…Gender differences have also been found to influence endorsement of social power strategies (Carli, 2001). Dunbar et al (2004) found that men and women differed in their effort to influence a peer's beliefs concerning the civil rights of ethnic minorities, with men using more hard influence strategies. In this study it was also found that efforts to influence a peer's beliefs about human rights was predicted by the endorsement of explicit ethnic and gender bias, as well as an orientation toward bias as measured on the Gough Pr measure.…”
Section: Peer Influence and Attitudes About Hate Crimesmentioning
confidence: 99%
See 3 more Smart Citations